The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0186972
|View full text |Cite
|
Sign up to set email alerts
|

Statins and new-onset atrial fibrillation in a cohort of patients with hypertension. Analysis of electronic health records, 2006–2015

Abstract: Hypertension is the most prevalent risk factor for new-onset atrial fibrillation (AF). But few studies have addressed the effect of statins on the incidence of this arrhythmia in patients with hypertension. This study aimed to evaluate the effect of statins on new-onset of this arrhythmia in a hypertensive population, accounting for AF risk. Data from the Information System for the Development of Research in Primary Care was used to recruit a retrospective cohort of ≥55-year-old hypertensive individuals with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In 2482 hypertensive patients with a mean age of 51 years and no initial pharmacological treatment, Verdecchia et al 19 found an AF rate of 4.6 per 1000 person-years. In contrast, Alvez-Cabratosa et al 29 observed an incidence rate that is more consistent with ours, of 12.5 per 1000 person-years in hypertensive www.nature.com/scientificreports www.nature.com/scientificreports/ patients in Spain. With regard to incidence by age group and sex, our results are concordant with those published elsewhere 26,27 : incidence is higher in men than in women and increases with age.…”
Section: Discussionsupporting
confidence: 89%
“…In 2482 hypertensive patients with a mean age of 51 years and no initial pharmacological treatment, Verdecchia et al 19 found an AF rate of 4.6 per 1000 person-years. In contrast, Alvez-Cabratosa et al 29 observed an incidence rate that is more consistent with ours, of 12.5 per 1000 person-years in hypertensive www.nature.com/scientificreports www.nature.com/scientificreports/ patients in Spain. With regard to incidence by age group and sex, our results are concordant with those published elsewhere 26,27 : incidence is higher in men than in women and increases with age.…”
Section: Discussionsupporting
confidence: 89%
“…A meta-analysis that compared studies with long versus short follow-up found no benefit of statins on AF in the trials with longer term follow-up. 40 Alves-Cabratosa et al 41…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis that compared studies with long versus short follow‐up found no benefit of statins on AF in the trials with longer term follow‐up . Alves‐Cabratosa et al evaluated the effect of statins on new‐onset of this arrhythmia in a hypertensive population, accounting for AF risk, and found that a limited protective effect of statins over new‐onset AF in this hypertensive population with no ischemic vascular disease, hypertensive patients would not benefit from statin use solely for AF primary prevention. J‐RHYTHM II study has found that there were no significant differences between an ARB (candesartan) and a CCB (amlodipine) in the development of persistent AF in the treatment of paroxysmal AF associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective 2006-2015 cohort of 100,276 hypertensive individuals aged ≥ 55 without ischemic vascular disease (of whom 9,814 initiated a statin), statin use conferred on a 9% reduction in AF incidence (0.91; 0.84-0.99) 31 . The absolute risk reduction increased with higher estimated risk; however, the relative risk of AF was similar and did not reach statistical significance across risk stratification.…”
Section: Patients With Stroke and Af Discharged On Statinmentioning
confidence: 99%